1994
DOI: 10.1073/pnas.91.9.3999
|View full text |Cite
|
Sign up to set email alerts
|

Two point mutations within the adducin genes are involved in blood pressure variation.

Abstract: The Milan hypertensive strain of rats (MHS) develops a genetic form of renal hypertension that, when compared to its normotensive control (MNS), shows renal dysfunction similar to that of a subset of human patients with primary hypertension. MHS and MNS were shown to be homozygous by multilocus miisatellite analysis and monolocus microsatellite markers. We show here that one point mutation in each of two genes coding for the membrane skeleton protein adducin is associated with blood pressure in the Milan strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
180
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(185 citation statements)
references
References 40 publications
3
180
0
2
Order By: Relevance
“…26 Several studies have addressed the question of whether carriers of the Trp allele of the a-adducin gene possibly contribute to the pathogenesis of essential hypertension. 7,12,[26][27][28][29][30][31][32] The overall evidence from these experimental and clinical studies indicates that Trp allele carriers have an increased risk of hypertension attributable to an innate stimulation of the sodium pump and enhanced renal tubular sodium reabsorption. 7,[33][34][35][36][37] However, most studies in humans suggest that mutation of the a-adducin gene on its own is insufficient to cause hypertension.…”
Section: Br Davis Et Almentioning
confidence: 99%
“…26 Several studies have addressed the question of whether carriers of the Trp allele of the a-adducin gene possibly contribute to the pathogenesis of essential hypertension. 7,12,[26][27][28][29][30][31][32] The overall evidence from these experimental and clinical studies indicates that Trp allele carriers have an increased risk of hypertension attributable to an innate stimulation of the sodium pump and enhanced renal tubular sodium reabsorption. 7,[33][34][35][36][37] However, most studies in humans suggest that mutation of the a-adducin gene on its own is insufficient to cause hypertension.…”
Section: Br Davis Et Almentioning
confidence: 99%
“…[5][6][7][8] Genetic differences in renal tubular salt reabsorption could thus contribute to the development of hypertension. [9][10][11][12][13][14] Cross-immunisation of cytoskeleton proteins between MHS and the normotensive rat strain (MNS) revealed immunochemical differences in an ␣/␤ heterodimeric protein called adducin. 15 Adducin is thought to interact with the actin cytoskeleton and could thereby be important for cell signalling.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Two mutations in the ␣-adducin and the ␤-adducin genes could explain up to 50% of the differ-which the frequency of the Trp460 allele was significantly lower in hypertensive patients than in normotensive controls (17.0% vs 21 ence in blood pressure between the MHS and the MNS. 9 Transfection studies with cDNA from the MHS showed altered ability of adducin to interact with actin and increased maximum velocity of the sodium-potassium pump. 18 In humans, polymorphic markers flanking the ␣-adducin gene have been shown to be associated with primary hypertension in Italians 19 and linkage has been demonstrated between the ␣-adducin locus and primary hypertension in French families.…”
Section: Introductionmentioning
confidence: 99%
“…1 The Gly460 → Trp polymorphism of an ␣-adducin subunit is associated with hypertension in French and Italian populations. 2 Blood pressure responses to acute salt-sensitivity tests and to chronic diuretic therapy were more pronounced in heterozygotes than in wild-type homozygotes.…”
Section: Introductionmentioning
confidence: 99%